Artificial Intelligence: implications for banking. (4th August 2014) - Mathawala, Yunus; Walter, Peter
This paper presents an overview of expert systems. It explains what an expert system is, and describes applications in the banking industry. Several examples of applications are cited. The importance of the utilisation of expert systems is stressed because these systems offer banks a competitive edge. Limitations and obstacles to implementation of expert systems are also covered.